SOCIAL-PSYCHOLOGICAL FORMATION MECHANISMS OF THE "IMAGE OF THE ENEMY" FROM UKRAINE BY THE RUSSIAN MASS MEDIA DURING THE RUSSIAN-UKRAINIAN WAR - Kholokh, Olena; Skriabin, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . Scientific research consists in the development of scientific knowledge about the moral and psychological aspects of war, one of which is the psychological phenomenon of the "image of the enemy" in the public consciousness of war participants, as well as the social and psychological mechanisms of its formation and transformation. The purpose and task of the research is to deepen the understanding of the psychological phenomenon of the "image of the enemy" in the social consciousness of a social subject. It is necessary to carry out a retrospective analysis of the socio-psychological mechanisms of the formation of the "image of the enemy" from Ukraine and Ukrainians in the public consciousness of Russians, using the example of coverage by Russian mass media of the ongoing Russian-Ukrainian war (2014-2023). Moreover, it is necessary to carry out a prospective analysis of the transformation of the "image of the enemy" in the public consciousness of Russians. M e t h o d s . In the research process, general scientific methods were used: analysis, synthesis, comparison and generalization. For an in-depth analysis of the psychological phenomenon of the "image of the enemy", the method of theoretical psychology – reconstruction – was used. Retrospective analysis was used to reveal the socio-psychological mechanisms of formation of the "image of the enemy" from Ukraine and Ukrainians in the public consciousness of Russians. The interdisciplinary approach made it possible to combine the results of philosophical studies in the field of border semiotics and the philosophical-anthropological understanding of the binary way of thinking of the images "We", "Others", "Strangers" and "enemies" in the public consciousness of the social subject and the previous results of this psychological research in order to carry out a prospective analysis of the transformation of the "image of the enemy" in the public consciousness of Russians. R e s u l t s . The "image of the enemy" in the public consciousness of Russians was formed in several stages. At the first stage, negative social, ethnic and cultural stereotypes of Ukraine and Ukrainians were formed. At the second stage, there was a direct formation of the "image of the enemy" in the public consciousness of Russians. The "image of the enemy" is expressed on the cognitive level (knowledge and beliefs about Ukrainians), the affective level (feelings and emotions about Ukrainians), and the behavioral level (reactions and actions about Ukrainians) of Russians. As a result of the prospective analysis, we can predict that the "image of the enemy" from Ukraine and Ukrainians formed in the public consciousness of Russians will transform in the future into the image of "Foreigners" or "Others". C o n c l u s i o n s . In the course of the conducted research, the understanding of the psychological phenomenon of the "image of the enemy" as a component of the social consciousness of the participants in the war was deepened. It performs a number of important functions and thereby contributes to the successful conduct of war in moral and psychological terms. In the vast majority of cases, the "image of the enemy" does not reflect reality, because it is artificially constructed thanks to socio-psychological mechanisms that use the means of mass communication. A retrospective analysis of the formation of the "image of the enemy" from Ukraine and Ukrainians in the public consciousness of Russians showed that the main socio-psychological mechanisms were: persuasion, manipulation and psychological contamination. The "image of the enemy" was formed at the cognitive level through the creation of narratives, at the affective and behavioral levels - thanks to fakes, simulacra and hate speech.